PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KURSI DECCO PADA PT KARYA CIPTA KREASI TANGERANG - Tuti Mutiara; Gojali Supiandi (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The purpose of this study is to find out the price and quality of the product on the purchase decision at PT Karya Cipta Kreasi. The method used in this study is quantitative descriptive with an associative approach. The sampling technique used is Probability Sampling, a sampling method using slovin theory. The analysis tool uses instrument testing, classical assumption testing, regression testing, autocorrelation and determination coefficient testing, and hypothesis testing. The results of the study concluded that there is a positive and significant influence both partially and simultaneously between price and product quality on the purchase decision at PT Karya Cipta Kreasi The results of this study are that price (X1) and product quality (X2) have a positive and significant effect on Consumer Satisfaction (Y) the resumption equation Y = 9.649 + 0.743 X1 The hypothesis test partially obtained a value of > or 8.137>1,664. It is therefore stated that it is rejected and accepted, so that it can be concluded that there is a significant influence between the price(X1) on the purchase decision (Y). The hypothesis test was partially obtained with a value of > or 6.943 > 1.664, then it was stated that it was rejected and accepted, there was a significant influence between product quality (X2) and the purchase decision (Y). The hypothesis test obtained a value of > or 40.529>3.11, then it was stated that it was rejected and accepted, so it can be concluded that there is a simultaneous influence between price (X1) and product quality (X2) on the purchase decision (Y) at PT Karya Cipta Kreasi Tangerang.